Narratives of Suffering and Endurance: Coercive Sexual Relationships, Truth Commissions and Possibilities for Gender Justice in Timor-Leste. (6th June 2014) - Kent, Lia
Abstract 1 : This article examines the narratives of 19 East Timorese women who were coerced into sexual relationships with members of the Indonesian security forces during the 24-year Indonesian occupation. Close attention to the key themes emerging from these stories helps to deepen understandings of women's diverse experiences of the conflict and postconflict periods, and sheds light on the gendered possibilities and limits of truth commissions. By destabilizing the therapeutic assumptions of truth commissions, these women's narratives also assist in developing a more contextualized, locally grounded and long-term approach to the pursuit of gender justice in Timor-Leste and elsewhere.